European Foreign Policy Research Reconsidered: Constructing an 'Ideal Power Europe' through Theory? - CEBECİ, EMİNE MÜNEVVER (SAGE PUBLICATIONS LTD, 2012)
This article attempts to criticise European foreign policy research from within, portraying how some of its scripts are privileged and how they construct an 'ideal power Europe' meta-narrative. It argues that European foreign policy researchers engage in such construction through, firstly, assuming that the EU is post-sovereign/post-modern; secondly, naming the EU as a model; and, finally, conceptualising the Union as a normative power. The article scrutinises European foreign policy research through a deconstruction of its texts and displays how certain knowledge about the EU and European foreign policy is produced and reproduced. It further reveals how the 'ideal power Europe' meta-narrative contributes to the dominative dimension of European foreign policy.
Keywords: deconstruction; European foreign policy research; identity; legitimacy; meta-narrative; NORMATIVE POWER; UNION; DIFFERENCE; RESISTANCE; IDENTITY; STATE